2014
DOI: 10.1007/s40618-014-0207-1
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of splice site mutation in 21-hydroxylase deficiency children

Abstract: The genetic analysis of the splice site mutation c.293-13A>G and c.518T>A variant can be used as good biomarkers for early detection of cases and carriers in 21-OHD CAH Egyptian children, since the methods used have rapid turnaround time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Some P450 SNPs are exceedingly rare, occurring in less than 1% of the population. These rare mutations are linked to congenital defects, including glaucoma (CYP1B1; Stoilov et al, 1998;Tanwar et al, 2009;Sheikh et al, 2014), 17-a hydroxylase deficiency (CYP17A1; Yamaguchi et al, 1998;Costa-Santos et al, 2004;Hwang et al, 2011;Qiao et al, 2011), congenital adrenal hyperplasia (CYP21A2; Robins et al, 2006;Lee, 2013;Szabó et al, 2013;Sharaf et al, 2015), spina bifida (CYP26A1; Rat et al, 2006), focal facial dermal dysplasia (CYP26C1; Slavotinek et al, 2013), and cerebrotendinous xanthomatosis (CYP27A1; Garuti et al, 1996;Verrips et al, 1997;Chen et al, 1998;Tian and Zhang, 2011). Other P450 polymorphisms that alter splicing are associated with neurologic and metabolic diseases, including Parkinson's disease (CYP2D6, Denson et al, 2005;CYP2J2, Searles Nielsen et al, 2013), hypertension (CYP4A11, Zhang et al, 2013;CYP17A1, Wang et al, 2011), breast cancer (CYP2D6, Huang et al, 1996;CYP19A1, Kristensen et al, 2000;) colon cancer (CYP2W1, Stenstedt et al, 2012), and lung cancer (CYP2D6, Huang et al, 1997;CYP2F1, Tournel et al, 2007).…”
Section: Snp-sensitive Alternative Splicing In the Cytochrome P450 Sumentioning
confidence: 99%
“…Some P450 SNPs are exceedingly rare, occurring in less than 1% of the population. These rare mutations are linked to congenital defects, including glaucoma (CYP1B1; Stoilov et al, 1998;Tanwar et al, 2009;Sheikh et al, 2014), 17-a hydroxylase deficiency (CYP17A1; Yamaguchi et al, 1998;Costa-Santos et al, 2004;Hwang et al, 2011;Qiao et al, 2011), congenital adrenal hyperplasia (CYP21A2; Robins et al, 2006;Lee, 2013;Szabó et al, 2013;Sharaf et al, 2015), spina bifida (CYP26A1; Rat et al, 2006), focal facial dermal dysplasia (CYP26C1; Slavotinek et al, 2013), and cerebrotendinous xanthomatosis (CYP27A1; Garuti et al, 1996;Verrips et al, 1997;Chen et al, 1998;Tian and Zhang, 2011). Other P450 polymorphisms that alter splicing are associated with neurologic and metabolic diseases, including Parkinson's disease (CYP2D6, Denson et al, 2005;CYP2J2, Searles Nielsen et al, 2013), hypertension (CYP4A11, Zhang et al, 2013;CYP17A1, Wang et al, 2011), breast cancer (CYP2D6, Huang et al, 1996;CYP19A1, Kristensen et al, 2000;) colon cancer (CYP2W1, Stenstedt et al, 2012), and lung cancer (CYP2D6, Huang et al, 1997;CYP2F1, Tournel et al, 2007).…”
Section: Snp-sensitive Alternative Splicing In the Cytochrome P450 Sumentioning
confidence: 99%
“…It was observed that about 65-75 % of the patients with CAH are compound heterozygotes [8]. Also, the most severe mutations (such as c.290-13A/C>G, c.515T>A and del c.329_336del) were not found among healthy controls [9] showing that genetic variants causing the most severe form of CAH are rare in general population.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Sharaf et al . [ 19 ] analyzed I2G mutation by allele-specific PCR and reported 76% and 17.2% cases with heterozygous and homozygous mutation respectively. Another study in Macedonia population report 41.5% of patient with I2G mutation by PCR/ACRS method.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately, 65–70% of CYP21A2 mutations are deleterious and due to microconversion derived from pseudogene CYP21A1P [ 18 ] including eight common mutations (p.P30L, c. 293-13A/C >G in intron 2 splice site, 8-bp deletion in exon 3, p.I172L, exon 6 cluster [p.I236N, p.V237E, p.M239K], p.V281L, p.Q318X, p.R356W). [ 19 ] About 25–30% are caused by unequal meiotic crossovers (or deletions). [ 18 ] Point mutations in compound state indicates SW form, although a single mutation has mild effect.…”
Section: Introductionmentioning
confidence: 99%